(untitled) (Journal of Sustainability, Environment and Peace, 2019)
Youth in Kenya have great potential and present a great resource with respect to sustainable development. Given an opportunity, they can and have demonstrated capability in ensuring peace and development. However, over the years, youth have been disengaged from normal productive activities in school, in the family and community. This goes on to increased youth involvement in armed crime which has only led to the death of youth, both innocent and criminals. The measures put in place to halt the prevalence of youth involvement in armed crimes have not been as successful. The Nyumba Kumi Initiative is a strategy of anchoring community policing at various levels that is household level, market, estate among others. This study is set to assess how effective the Nyumba Kumi policing initiative is in Kenya. This is in terms of governance i.e inclusivity of the youth. The study took place in Kayole, Nairobi County. Data was acquired through administering of questionnaires and Key Informant Interviews. A total of 300 questionnaires were administered. The primary data was subjected to qualitative and quantitative analysis. Several key findings observed include inter alia; Lack of inclusivity of the youth in community policing initiatives. Keeping in mind that community intelligence is the best intelligence, this research would enhance the existing structures of the Nyumba Kumi Initiative for improved human security.